Digital Asset Analysis, Design, Develop And Deliver For LMS According To Scorm Standard, Case Study: Vocational High School Of Software Engineering - Migunani Migunani (Lembaga Pengembangan Kinerja Dosen, 2023)
In this study, we evaluated the limitations of using learning resources that can be used in a Learning Management System (LMS) platform, which cannot be packaged and can be used again in processing, combining, and rearranging learning based on learning objects that already exist in different LMS platforms. Studying content with formats other than SCORM is not easy adapted to the needs because the content must be reorganized every time using a different platform. Therefore, it is necessary to analyze and design learning according to the SCORM format to meet the ISO 19796-1 standard platform. This standard has the ability to share, reuse, and interoperate learning objects. The challenge in the world of education today is how to build a knowledge-based society. The building of e-learning plays an important role. Currently, the e-learning portal is a very diverse learning management system (LMS) platform used by schools or tertiary institutions. In addition, the types of learning resources and content are also diverse. It does not meet the e-material design requirements based on mechanisms that can be shared, reused, and operated on different platforms to meet the granularity element. The results provide insight and highlight the mismatch between digital learning and digital asset standards, especially in Indonesia. This helps us analyze, design, develop, and submit digital assets for electronic learning materials in vocational high school software expertise programs in accordance with SCORM Standards.